2008
DOI: 10.1007/s10509-008-9824-5
|View full text |Cite
|
Sign up to set email alerts
|

Shock waves in a dusty plasma with dust of opposite polarities

Abstract: A four-component dusty plasma consisting of electrons, ions, and negative as well as positive dust particles has been considered. The basic features of shock waves that may exist in such a four-component dusty plasma have been theoretically investigated by the reductive perturbation method. The implications of our results in different regions of space (viz. cometary tails, mesosphere, Jupiter's magnetosphere, etc.) are briefly discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Based on theoretical prediction and satellite observations, Mamun and Shukla [22] theoretically investigated the properties of linear/nonlinear electrostatic waves for a very simple dusty plasma system, which contains Maxwellian electrons-ions and inertial opposite polarity charged dust. Considering different dusty plasma models with dust of opposite polarity have been investigated [23][24][25] by many authors. It has been observed that the presence of additional positive dust component not only significantly modify the vital properties of solitary structures but also causes the coexistence of positive and negative potentials solitary structures.…”
Section: Introductionmentioning
confidence: 99%
“…Based on theoretical prediction and satellite observations, Mamun and Shukla [22] theoretically investigated the properties of linear/nonlinear electrostatic waves for a very simple dusty plasma system, which contains Maxwellian electrons-ions and inertial opposite polarity charged dust. Considering different dusty plasma models with dust of opposite polarity have been investigated [23][24][25] by many authors. It has been observed that the presence of additional positive dust component not only significantly modify the vital properties of solitary structures but also causes the coexistence of positive and negative potentials solitary structures.…”
Section: Introductionmentioning
confidence: 99%
“…Mamun (2008) found that the presence of additional positive dust particles does not only significantly modify the basic properties of solitary potential structures, but also causes the coexistence of positive and negative solitary potential structures. All of these works Mamun 2008;Rahman et al 2008) were beyond the scope of the head-on collision between two DASWs in a dusty plasma. Currently, in the process of soliton propagation in dusty plasmas, wave-wave interaction represents one of the most interesting and important nonlinear phenomenon in modern plasmas researches.…”
Section: Introductionmentioning
confidence: 99%
“…Wave propagation in such complex systems is therefore expected to be substantially different from the ordinary two component plasmas and the presence of charged dust can have a strong influence on the characteristics of the usual plasma wave modes, even at frequencies where the dust grains do not participate in the wave motion. Among the host of new dusty modes discussed in the literature, the dust-acoustic wave (DAW) (Rao et al 1990) has received wide attention (Mamun 1999a(Mamun , 1999bGhosh et al 2001;El-Labany et al 2002, 2010Rahman et al 2008;Pakzad 2010;Das and Devi 2010;Tribeche and Benzekka 2011) as well as experimental confirmation (Barkan et al 1995) in several low-temperature dusty plasma devices. The later arises due to the restoring force provided by the plasma thermal pressure (electrons and ions) while the inertia is due to the dust mass.…”
Section: Introductionmentioning
confidence: 99%